Pengaruh Penggunaan Peta Konsep terhadap Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran IPA Materi Sifat-Sifat Cahaya di Kelas 5 SD Alwashliyah 31 Tahun Ajaran 2024/2025 - Rudi Hermansyah Sitorus; Muhammad Dekar; Zulvia Misykah; Belia Tama Heppi (Dharma Acariya Nusantara Jurnal Pendidikan Bahasa dan Budaya, 2026)
This study aims to analyze the effect of concept mapping on students’ critical thinking skills in science learning, particularly on the topic of light properties. The research employed a quasi-experimental design involving two groups: an experimental group using concept mapping and a control group using conventional teaching methods. The sample consisted of 71 fifth-grade students at SD Al-Washliyah 31. Data were collected through pretest and posttest Instruments developed based on Bloom’s revised taxonomy to measure students’ critical thinking skills. The results showed that students in the experimental group demonstrated a significant improvement in critical thinking skills compared to those in the control group. Statistical analysis using an independent t-test indicated a significant difference (p < 0.05) between the two groups. Concept mapping helps students organize knowledge systematically, understand relationships between concepts more clearly, and enhance their analytical thinking skills. Therefore, it can be concluded that concept mapping is an effective learning strategy to improve students’ critical thinking skills in science learning contexts.